Test–Retest Reliability of the Brain Metabolites GABA and Glx With JPRESS, PRESS, and MEGA‐PRESS MRS Sequences in vivo at 3T. Issue 4 (30th October 2019) - Baeshen, Arwa; Wyss, Patrik O.; Henning, Anke; O'Gorman, Ruth L.; Piccirelli, Marco; Kollias, Spyridon; Michels, Lars
Abstract : Background: The optimization of magnetic resonance spectroscopy (MRS) sequences allows improved diagnosis and prognosis of neurological and psychological disorders. Thus, to assess the test–retest and intersequence reliability of such MRS sequences in quantifying metabolite concentrations is of clinical relevance. Purpose: To evaluate the test–retest and intersequence reliability of three MRS sequences to estimate GABA and Glx = Glutamine+Glutamate concentrations in the human brain. Study Type: Prospective. Subjects: Eighteen healthy participants were scanned twice (range: 1 day to 1 week between the two sessions) with identical protocols. Field Strength/Sequence: 3T using a 32‐channel SENSE head coil in the PCC region; PRESS, JPRESS, and MEGA‐PRESS sequences. Assessment: Metabolite concentrations were estimated using LCModel (for PRESS and MEGA‐PRESS) and ProFit2 (for JPRESS). Statistical Tests: The test–retest reliability was evaluated by Wilcoxon signed‐rank tests, Pearson's r correlation coefficients, intraclass‐correlation coefficients (ICC), coefficients of variation (CV), and by Bland–Altman (BA) plots. The intersequence reliability was assessed with Wilcoxon signed‐rank tests, Pearson's r correlation coefficients, and BA plots. Results: For GABA, only the MEGA‐PRESS sequence showed a moderate test–retest correlation ( r = 0.54, ICC = 0.5, CV = 8.8%) and the BA plots indicated good agreement ( P > 0.05) for all sequences. JPRESS provided less precise results and PRESS was insensitive to GABA. For Glx, the r and ICC values for PRESS ( r = 0.87, ICC = 0.9, CV = 2.9%) and MEGA‐PRESS ( r = 0.70, ICC = 0.7, CV = 5.3%) reflect higher correlations, compared with JPRESS ( r = 0.39, ICC = 0.4, CV = 20.1%). Data Conclusion: MEGA‐PRESS and JPRESS are suitable for the reliable detection of GABA, the first being more precise. The three sequences included in the study can measure Glx concentrations. Level of Evidence : 2 Technical Efficacy : Stage 1 J. Magn. Reson. Imaging 2020;51:1181–1191.